Reconfiguration of Reo Connectors Triggered by Dataflow - Koehler, Christian; Costa, David; Proenca, Jose; Arbab, Farhad (Electronic Communications of the EASST, 2008)
Reo is a language for coordinating autonomous components in distributed environments. Coordination in Reo is performed by circuit-like connectors, which are constructed from primitive, mobile channels with well-defined behaviour. While the structure of a connector can be modeled as a graph, its behaviour is compositionally defined using that of its primitive constituents. In previous work, we showed that graph transformation techniques are well-suited to model reconfigurations of connectors. In this paper, we investigate how the connector colouring semantics can be used to perform dynamic reconfigurations. Dynamic reconfigurations are triggered by dataflow in the connector at runtime, when certain structural patterns enriched with dataflow annotations occur. For instance we are able to elegantly model dynamic Reo circuits, such as just-in-time augmentation of single-buffered channels to a circuit that models a channel with an unbounded buffer. Additionally we extend Reo’s visual notation and the Reo animation language to describe and animate dynamically reconfiguring connectors.